O szczególnych powinowactwach literatury i kina w refleksji Stefanii Zahorskiej - Hendrykowska, Małgorzata (Przestrzenie Teorii, 2019)
Hendrykowska Małgorzata, O szczególnych powinowactwach literatury i kina w refleksji Stefanii Zahorskiej [Particular Affinities between Literature and Film in Stefania Zahorska’s Reflections]. „Przestrzenie Teorii” 32. Poznań 2019, Adam Mickiewicz University Press, pp. 167–178. ISSN 1644-6763. DOI 10.14746/pt.2019.32.8. The author provides an in-depth analysis of and original essay written by the Polish film critic Stefania Zahorska in the middle of the 1930s. The essay deals with socio-cultural and aesthetic theory regarding the mutual connections between cinema and literature.